Routine use of progesterone does not prevent miscarriage. (8th November 2019) - Cook, Rob; Thomas, Vaughan; Taft, Rachel
The study: Coomarasamy A, Devall AJ, Cheed V, et al. A randomised trial of progesterone in women with bleeding in early pregnancy N Engl J Med 2019;380:1815-24. This project was funded by the NIHR Health Technology Assessment Programme (project number 12/167/26). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000792/miscarriage-not-prevented-by-routine-use-of-progesterone